GLP-1 Receptor Agonists: Therapeutic Benefits in Renal Function, Cardiovascular Risk, and Physical Activity - A Systematic Review - Łukasz Karaban; Tadeusz Kuźnieców; Monika Paszkowska; Klaudia Mularczyk; Michał Borawski; Aleksandra Ciuła; Anna Jakubiak; Joanna Miśkiewicz; Patrycja Znamirowska; Magdalena Kupis (Quality in Sport)
Introduction: Type 2 diabetes is one of the greatest challenges of modern medicine. Its growing prevalence and numerous complications, especially cardiovascular ones, demand constant improvement of treatment strategies. Cardiovascular disease remains the leading cause of death in these patients, highlighting the importance of therapies that address both glycaemic control and cardiovascular risk.